M6A Modification and Transcription Analysis of LncRNA in Cerebral Ischemia/Reperfusion Injury - Jierong Mo; Zhiquan Li; Zhengfei Yang; Zuhua Huang; Pengpeng Guo; Jianfeng Gao; Haiqiong xiao; Ping Ye; Haini Qin; Tianen Zhou; Jun Jiang (International Journal of Genomics)
LncRNA is a major factor in the occurrence and development of many diseases. However, its mechanism in cerebral ischemia/reperfusion injury (CIRI) is yet unknown. In this study, the transcriptional level and methylation modification level of LncRNAs before and after mechanical thrombectomy were compared by high-throughput sequencing. Venn diagram, Spearman correlation analysis, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, TargetScan, and miRanda were used to analyze the experimental data. The results showed that four key LncRNAs changed at both transcription and methylation levels. Specifically, LncRNA FAR2, LINC02431, and AL357060.1 were downregulated and hypomethylated, while LncRNA FOXD2-AS1 was upregulated and hypomethylated. Moreover, positive regulation of angiogenesis, protein domain–specific binding, autophagy pathway, PPAR signaling pathway, and MAPK signaling pathway were co-enriched between LncRNAs with different expression levels and different methylation levels. Finally, a LncRNA-miRNA-mRNA network was constructed. Therefore, this study explored the potential key LncRNAs and regulatory mechanisms of CIRI.